Missio hominum as commissioned by missio Dei - Thinane, Jonas Sello (HTS teologiese studies, 2022)
The Christian image of God rightly goes back to the Bible as the only source of revelation. According to the creation account in the book of Genesis, God is primarily seen as the creator of heaven, Earth and humankind. Following this understanding, the International Mission Conference (IMC) in Willingen in 1952 expanded the scope of mission beyond the ecclesiastical sphere and anchored it in the doctrine of the Triadic God. In other words, the Willingen Conference correctly classified the Triadic God as the only source of mission in the world. However, the question remains as to what a person’s mandate is in relation to the missio Dei. Based on a literature review, this article introduces missio hominum as a framework that encompasses human participation in missio Dei. Selectively, the extraordinary personalities of Noah, Jesus Christ and the Apostle Paul in the Bible are examined in order to validate the framework of the missio hominum as derived from the missio Dei. By its very nature, this article warrants further exploration of human involvement in the work of the missio Dei, in order to consolidate the missio hominum as an important framework for aligning human efforts with the work and ultimate goal of the missio Dei.Contribution: The contribution of this article is to deepen the reflection on the relationship between the Triadic God and human beings on the one hand and human temporal participation in the eternal economy of the missio Dei on the other. In doing so, it provides missio scholars and theologians with new insights that encompass the human mission in relation to the missio Dei.